Training Santri in Inventory Management with Spreadsheet Technology - Agus Setiawan; Agung Setiawan; Ahmad Mufti; Asker Haidil Mochtar; Muhammad Dinar Ryaldi Kusuma (SocietalServe: Journal of Community Engagement and Services, 2025)
This community service program was designed to enhance the inventory management skills of santri at Pesantren Assyifa through the use of spreadsheet technology. Many pesantren-based business units still rely on manual inventory methods, leading to inefficiencies, stock errors, and operational delays. To address this issue, a structured training program was conducted involving 25 selected santri actively engaged in the pesantren’s economic units. The program consisted of three interactive sessions covering basic inventory concepts, spreadsheet functions, and hands-on design of inventory tracking systems. Using tools like Microsoft Excel and Google Sheets, participants were guided to create real-time stock records, calculate inventory movement, and generate reports. The success of the training was measured through pre- and post-tests, spreadsheet project submissions, and participant feedback surveys. The results showed a 68% average increase in test scores, a 96% project completion rate, and a 4.6/5 satisfaction score. Additionally, 84% of participants applied the system directly within pesantren business units. Feedback from participants indicated high engagement, practical usefulness, and a strong desire for follow-up training. This initiative demonstrated the effectiveness of integrating digital tools into pesantren education, contributing to the development of digitally literate and economically empowered santri.